Metallimalmikaivosten vesistövaikutukset : esimerkkinä Talvivaaran kaivoksen sulfaatti-, natrium- ja mangaanipäästöt - Ratava, Paula (2013)
Mining industry is expanding in Finland and it is expected to become a forerunner in taking environmental issues into account in its processes. Mines often lower the water quality of their surrounding waters and this may lead to salinization and eutrophication for instance. Salinization may be due to dissolved ions in the wastewater, like sulphate and sodium, and may cause the artificial stratification of a lake. Sulphate can also prevent the natural circulation of iron in the sediments, which favors the release of phosphorus and could lead to eutrophication. All impacts cannot be assessed in advance and not enough studies have been made concerning these substances. The Talvivaara mine in Sotkamo is an example of a new technology, bioleaching, where nickel is being extracted of the ore with the help of microbes. The discharges of e.g. sulphate, sodium and manganese to nearby waters have been larger than expected, which has caused challenges to the water balance and the wastewater management. The aim of this study was to examine the changes in the concentrations of these substances from the measurements carried out by the consultant company from 2007, before the mine, until September 2012, to compare these concentrations to other Finnish lakes and to study the impacts on waters from the point of view of salinization and eutrophication. To analyze the possibility of eutrophication the concentration of phosphorus in the deeper water layers was compared to the concentrations of sulphate, oxygen and iron. In small-scale field studies two lakes were studied by water and sediment samples. In this study it was clear that still in 2012 the concentrations of sulphate, sodium and manganese especially in the deepest water layers were higher and differed from other Finnish lakes. Salinization and oxygen depletion were seen clearly in the closest lakes to the mine at latest during the year 2012, when also the concentrations of Fe and P rose. Layers of sulphides in the sediment samples and the rising P-concentration could indicate sulphate-mediated eutrophication, however, the Fe/P-ratio was still sufficient to keep the phosphorus in the sediment. More studies could be carried out on the links between the wastewater, its management, watersheds and the situation in the bottom of the lakes and, in general, on the impacts of these substances on waters.